2004
DOI: 10.1051/jbio/2004198010037
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies de la prise alimentaire chez la souris dépourvue de récepteur 5-HT4

Abstract: Reçu le 5 janvier 2004 RÉSUMÉ Nous avons généré des souris invalidées pour le gène codant le récepteur 5-HT, de la sérotonine (5-HT) pour en étudier les implications fonctionnelles. L'absence de ce gène dès la période embryonnaire a rendu les souris adultes mâles hyposensibles aux stress anorexigènes (stress de contrainte). Nos don nées récentes ajoutent que l'inactivation pharmaco logique du récepteur 5-HT4 après une administration systémique du RS39604 (0,5 mg/kg) a supprimé l'ano rexie due au stress de cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…However, acute stress has been reported to reduce cumulative food intake, while increasing corticosterone in rodents . Another study also showed that restraint stress has also been shown to induce a marked decrease of food intake in wild‐type mice . These studies reveal that corticosterone may play an important role in feeding behavior.…”
Section: Introductionmentioning
confidence: 88%
“…However, acute stress has been reported to reduce cumulative food intake, while increasing corticosterone in rodents . Another study also showed that restraint stress has also been shown to induce a marked decrease of food intake in wild‐type mice . These studies reveal that corticosterone may play an important role in feeding behavior.…”
Section: Introductionmentioning
confidence: 88%